Peer versus coping models: The influence on children's self-efficacy beliefs, perceived task difficulty and diving performance. - Clark, Shannon E. (University of Ottawa (Canada), 2001)
The purpose of this experiment was to examine the influence of peer mastery and peer coping models on children's self-efficacy beliefs, perceptions of task difficulty and diving performance. Thirty children (M age = 7.7, SD = 2.3) who did not yet know how to dive and who were identified as having low feelings of self-efficacy towards diving and high perceptions of diving task difficulty were randomly assigned to peer mastery, peer coping or control model conditions. The experiment took place over 4 days. On the first three days the participants were exposed to their assigned modeling condition and then received diving instruction. After the last intervention session there was an immediate-retention test and the following day there was a delayed-retention test. Prior to intervention and for both retention tests, two psychological dimensions and one physical performance measure were evaluated. As well, recognition performance was evaluated during the delayed-test only. Data were analyzed by four separate one way analyses of variance for Group. Results revealed that the peer coping group increased their self-efficacy beliefs more than the peer mastery group in the delayed-retention test F = (2, 29) = 3.9, p = 0.03. The small sample size and the large variance in each group resulted in the inability to find other statistical findings. Effect sizes were then calculated. This analysis revealed that there were no significant effects between groups in the recognition performance test. The analysis did show that the peer coping group was the better model group for increasing children's perceptions of task difficulty and self-efficacy beliefs towards diving. For diving performance, peer mastery group showed the greatest increases. These findings suggest that a peer mastery model provides more information to the learner about how to do the skill correctly, whereas a peer coping model benefits a learner's psychological responses to observational learning.
Keywords: Education, Physical.